CD10 and p63 expression in a sarcomatoid undifferentiated melanoma: A cautionary (and molecularly annotated) tale. (20th January 2020) - Lefferts, Joel A; Loehrer, Andrew P.; Yan, Shaofeng; Green, Donald C.; Deharvengt, Sophie J.; LeBlanc, Robert E.
Abstract: Undifferentiated melanoma should be considered in the differential diagnosis of sarcomatoid cutaneous malignancies to ensure that patients receive the correct treatment. Dermatopathologists should recognize the pitfalls of relying too heavily on immunohistochemistry to establish this diagnosis and consider ancillary tests, including single‐nucleotide polymorphism (SNP) copy number arrays and targeted next‐generation sequencing (NGS), when a definitive diagnosis cannot be rendered on a primary or metastatic tumor. This technology can also help to exclude a collision of melanoma and sarcoma when both differentiated and undifferentiated components are juxtaposed. We describe an exceedingly rare, illustrative example of undifferentiated sarcomatoid melanoma presenting as a pedunculated nodule. The clinical context and presence of a small differentiated component helped to establish the diagnosis; however, the transition from differentiated to undifferentiated melanoma was accompanied by an abrupt loss of S100, Sox10, MITF, MelanA, and HMB45 with gain of CD10 and p63 staining. SNP copy number array and NGS revealed shared chromosomal copy number changes and overlapping mutations with additional aberrances detected exclusively in the sarcomatoid component, thereby excluding a collision tumor and confirming our putative impression of melanoma with progression to an undifferentiated sarcomatoid phenotype.